Analysis of Service Quality on Customer Satisfaction of Barge Ship Repair Services Case Study PT. Galangan Anugerah Wijaya Succeeds Using Smartpls and SPSS Methods - Wijoyo, Afif Wibisono; Santosa, Ari Wibawa; Mursid, Ocid (Jurnal Teknik Perkapalan, 2024)
ABSTRACT In a service business, assessing service quality is very important and influences consumer perceptions and expectations. Customer satisfaction is the goal and means of marketing.Customer satisfaction can be achieved if the company provides what the customer wants and needs. Therefore, customer satisfaction is very important for service companies. Formulating service quality requires customer aspirations to encourage company innovation and creativity inimproving service quality. The aim of this research is to determine aspects of customer service and determine the sustainability of repair services at PT. Galangan Anugerah Wijaya Berjaya Determination of service variables was obtained using the Smartpls calculation method using SPSS software. In data processing there are several stages, namely observation, interviews, distributing questionnaires, processing respondent characteristics based on length of subscription and education. The results of this research show that there is an influence of shipyard service quality on customer satisfaction. The results of the questionnaire answers showthat PT. The Anugerah Wijaya Berjaya Shipyard serves carefully and the shipyard's service quality is 2,638, thus having a significant influence on customer satisfaction.